Implementasi Kurikulum Merdeka dalam Pembelajaran Pendidikan Agama Islam pada Anak Tunagrahita Ringan di SLB Negeri Bina Bangsa Syamtalira Aron Aceh Utara - Mauliza, Iqlima; Yusnaini, Yusnaini; Safitri, Maya (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to describe the implementation of the Merdeka Curriculum in teaching Islamic Religious Education (PAI) to children with mild intellectual disabilities at SLB Negeri Bina Bangsa. Children with mild intellectual disabilities have intellectual limitations that require a more individualized, concrete, and contextual learning approach. Within the context of the Merdeka Curriculum, teachers are expected to design differentiated, enjoyable, and student-centered learning activities. This research uses a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation, conducted at SLB Negeri Bina Bangsa Syamtalira Aron and an SLB in Lhokseumawe city. The results show that PAI learning is implemented through concrete approaches involving direct practice, storytelling, role-playing, the use of visual media, and habituation of religious values. Evaluation is carried out qualitatively and authentically through observation of students’ religious behavior. The Merdeka Curriculum provides teachers with the creative freedom to adapt content, processes, and assessments to meet the needs of students with mild intellectual disabilities. This implementation also reflects humanistic principles and learning consistent with modern curriculum theories. The findings confirm that the Merdeka Curriculum can be effectively applied in inclusive education, provided there is support from creative teachers, adequate learning facilities, and active involvement of parents and the school environment.